NUEVOS Y ELOCUENTES RESTOS CRANEANOS DE PROBORHYAENA GIGANTEA AMEGHINO, 1897 (MARSUPIALIA, BORHYAENIDAE, PROBORHYAENINAE) DE LA EDAD DESEADENSE. UN EJEMPLO DE COEVOLUCIÓN (Ameghiniana, 2013)
NEW AND ELOQUENT CRANIAL REMAINS OF THE DESEADAN (EARLY OLIGOCENE) Proborhyaena gigantea AMEGHINO, 1897 (MARSUPIALIA, BORHYANIDAE, PROBORHYAENINAE). AN EXAMPLE OF COEVOLUTION. - The most complete remains of tbe Deseadan (Early Oligocene) giant marsupial Proborhyaena gigantea Ameghino, 1897 (Borhyaenidae, Proborhyaeninae ) are described. These remains, together with different remains since long known, allow to recognize for the first time most of the unique carnivore dental adaptations that characterize this peculiar marsupial: (1) short rostrum; (2) C1 hipertrofied, "saber-tooth" like, but ovoidal in section, not blade-líke, (3) c1, unusually enlarged; (4) cheek-teeth series complete: P1,2/P1_2 inserted obliquely, almost transversely; P3/P3 enlarged; M1_3 with reduced protocone and extended shearing metacrist. Suggestively this peculiar carnívorous marsupial coexisted with very large-sized herbivorous (Edentata and "ungulates" s.l.), and all became extinct simultaneously. The differentiation and extinction of those gigantic predator and herbivores appear to be a conspicuous South American example of coevolution. The extinction of these huge mammals, together with the extinction of many other relatively giant and striking mammals, mark the end of the Deseadan Age, it is interpreted as the effect of decisive climatic-environmental changes, the same that affected similarly the mammal communities all over the world.